Channel Codıng Technıque In 5G Radıo Network - B.Yamini Pushpa, Dr. Sunita panda (International Journal of Advanced Science and Technology, 2020)
Eminent LDPC codes have appreciated performance with large block length and high code rate, which makes use in current wireless applications. Although LDPC codes show underlying performance for short block lengths and low code rates which are essential for 5G scenarios. There is inherent requisite for channel coding in 5G scenarios to support variable code rates and code lengths with high throughput, low tolerance, low energy and low decoding efficiency. The codes which satisfy all the above requirements are polar codes. This paper presents comparison of turbo codes, LDPC codes and polar codes at the introduction part and usage of polar codes in different scenarios